2017
DOI: 10.1017/s0950268817002679
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an intervention programme on knowledge, attitudes and practices of population regarding severe fever with thrombocytopenia syndrome in endemic areas of Lu'an, China

Abstract: Knowledge, attitudes and practices (KAP) of the population regarding severe fever with thrombocytopenia syndrome (SFTS) in endemic areas of Lu'an in China were assessed before and after an intervention programme. The pre-intervention phase was conducted using a sample of 425 participants from the 12 selected villages with the highest rates of endemic SFTS infection. A predesigned interview questionnaire was used to assess KAP. Subsequently, an intervention programme was designed and applied in the selected vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…For all participants, scores for each dimension of KAP were analyzed as the number of points obtained as a proportion of the maximum possible score [12,26]. We combined KAP data with previously collected data on serostatus for leptospirosis, demographic, socioeconomic, and environmental/exposure factors [7,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all participants, scores for each dimension of KAP were analyzed as the number of points obtained as a proportion of the maximum possible score [12,26]. We combined KAP data with previously collected data on serostatus for leptospirosis, demographic, socioeconomic, and environmental/exposure factors [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…For questions on attitudes and practices, we used a three-point Likert scale [25,26]. For each question on satisfactory attitudes, a "yes" answer was given a score of 2, "maybe" a score of 1, and "no" was given 0 score.…”
Section: Data Collectionmentioning
confidence: 99%
“…The SFTS knowledge level reported in this study was 37.4%, which is lower than the 56.2% reported in another KAP study conducted in Lu'an city, another area of Anhui Province in which SFTS is prevalent. 21 This low SFTS knowledge level may be due to the lack of regular health education programs in our study settings and limited information sources regarding SFTS. In our study, we further demonstrated that even though participants had heard about SFTS, knowledge of the symptoms and signs was lacking.…”
Section: Discussionmentioning
confidence: 83%
“…Most respondents expressed the appropriate attitude of visiting a doctor immediately when bitten by a tick, a finding which is similar to that of a previous KAP study on zoonotic disease. 21 Participants with lower knowledge levels have been shown to be more likely to have a right attitude toward the disease. 23 In this study, more than 80.0% of participants desired consultation and nearly 70.0% were willing to attend the free detection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the case fatality rate has decreased, its epidemic area has continued to expand. 23 provinces in China reported SFTS cases, and the absolute number of infections increased from 2010 to 2016 [ 3 ]. Even in 2017, more than 90% of SFTS cases reported in China and the World Health Organization once listed SFTS as one of the nine major infectious diseases in the key list, which is one of the most serious public health problems in recent years [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%